Pembelajaran pendidikan jasmani didasarkan pada proyek dasar untuk meningkatkan literasi dan numerasi siswa - Hakim, Luqmanul; Mulyono, Mulyono; Dharma Utamayasa, I Gede; Triatmojo, Muhammad; Indah Megawati, Putri (Universitas Nusantara PGRI Kediri, 2023)
Numerical literacy in early can be used as a tool for developing thinking skills in children, supporting children in developing various talents or intellectual potentials they have, and can be used as a means of cultivating a positive affective side in instilling basic personality. This study aims to describe numeracy literacy skills in early childhood students. This research aims to improve students' reading and numeracy skills through learning about physical education and health. The method used is quantitative. The approach used is an experimental pretest-posttest design. The simple random sampling technique was divided into 2 groups of 50 students in the experimental group and 50 in the control group. This type of research is population research. The data are analyzed by using paired sample t-test with a significance level (p<0.05). Based on the analysis and discussion results, using the learning model using the project with a combination of mathematics and sports can improve literacy and numeracy skills in junior high school students in Bondowoso Regency, East Java. Based on data analysis, the following results were obtained: (1) There was a significance in literacy with sig 0.000 values; (2) There was a significance in numeracy with sig 0.002; (3) There was a significance in the control group with sig 0.000. So that through this research, the expected indicators in the implementation of literacy and numeracy in mathematics and sports can be achieved by students. Project-based learning is beneficial for students and provides motivation.